The Moderating Role of Corporate Governance on Financial Ratio, Firm Size and Tax Avoidance at Indonesian Sharia Companies - Winarto, Wahid Wachyu Adi (Universitas Muhammadiyah Semarang, 2023)
In this study, corporate governance will be used as a moderating variable to experimentally evaluate the relationship between leverage, firm size, and tax avoidance. Companies are currently engaging in some tax avoidance to limit the tax levied against them. This can impact how much income the company acquires, which in turn lowers the share profit distributed to stakeholders. A Sharia company registered with JII 70 makes up the study population using an associative quantitative research approach. The SPSS application is used in data analysis methods. The findings indicated that the profitability variable directly impacted tax avoidance, whereas the leverage variable had no bearing and the firm size variable had an impact. The results of the indirect effect analysis, namely moderation analysis, found that corporate governance moderates the relationship between profitability and firm size with tax avoidance, and corporate governance cannot moderate the relationship between leverage and tax avoidance.